Using technology, reflection, and noticing to promote intercultural learning during short-term study abroad. Issue 1 (14th March 2021) - Lomicka, Lara; Ducate, Lara
Abstract: While intercultural learning is a key goal of study abroad, it is often difficult to assess or even achieve. Recent models, such as linguistic landscapes (which looks at the language of public signs, including road signs, advertising billboards, street, and place names), can help students reflect on and make sense of their intercultural experiences in more intentional ways. By working through tasks based on the four areas of social pedagogies, which serves as the framework for this study, students became more aware of their surroundings and documented their linguistic landscape visually and in digital form. They posted their findings to Padlet, a social media tool, which allowed students access to a collaborative and co-constructive participatory culture. Open coding was used to identify two themes that emerged from the data: (1) students became aware of their surroundings; and (2) students developed a sense of cultural awareness. We also comment on how students reflected on the project. Students noticed otherwise unobvious aspects of culture and used those observations to shape their own ideas about the target culture as they worked toward constructing an intellectual community through engagement with different perspectives. Finally, students gained skills in intercultural learning as they reevaluated both their own and the target cultures while considering new perspectives as well as historical and cultural contexts.